2022
DOI: 10.3390/children9091358
|View full text |Cite
|
Sign up to set email alerts
|

Drama Therapy for Children and Adolescents with Psychosocial Problems: A Systemic Review on Effects, Means, Therapeutic Attitude, and Supposed Mechanisms of Change

Abstract: Drama therapy is applied to children and adolescents with psychosocial problems. Drama therapy is an experimental form of treatment which methodologically uses drama and theatre processes to achieve psychological growth. Although in clinical practice, drama therapy has been applied successfully, little is known about how and why drama therapy contributes to a decrease in psychosocial problems. A systematic narrative review was performed to obtain more insight into this issue. Eight databases were systematicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…The authors found benefits for emotional, psychological, and social development in this population. Yet another systematic review examined drama therapy for children and adolescents with psychosocial problems (Berghs et al, 2022). The nine studies included in the review consisted of four RCTs, three CCTs, and three studies with a single group pre-post design.…”
Section: Previous Reviews Of Drama Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…The authors found benefits for emotional, psychological, and social development in this population. Yet another systematic review examined drama therapy for children and adolescents with psychosocial problems (Berghs et al, 2022). The nine studies included in the review consisted of four RCTs, three CCTs, and three studies with a single group pre-post design.…”
Section: Previous Reviews Of Drama Therapymentioning
confidence: 99%
“…Thus overall, the evidence for the effectiveness of drama therapy is mounting, with a clear prevalence of qualitative designs and an underrepresentation of robust RCTs. Five reviews used the recommended PRISMA guidelines and flow diagram to clearly convey their search process (Berghs et al, 2022; Bololia et al, 2022; Bourne et al, 2018; Feniger-Schaal & Orkibi, 2020; Leather & Kewley, 2019). Quality or risk of bias assessments was conducted in five reviews (Berghs et al, 2022; Bololia et al, 2022; Feniger-Schaal & Orkibi, 2020; Leather & Kewley, 2019; Ruddy & Dent-Brown, 2007).…”
Section: Drama-based Therapies For Mental Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the role-play, the client acts to separate themself from their anxiety problem and allows themself to externalise their anxiety, rather than internalising the anxiety. Drama therapy (ET) can reduce psychosocial problems in children and adolescents, with a reduction in depressive symptoms, (social) anxiety, post-traumatic stress, inattention (especially on hyperactivity and impulsivity), aggressive behaviour such as hostility, violent behaviour, in addition to an increase in assertiveness, a positive effect on learning behaviour and on school abilities (Berghs et al, 2022).…”
Section: Formulating the Mi-et Framework For Adolescent Counsellingmentioning
confidence: 99%
“…While they determined that dramatherapy is an effective treatment for a number of populations, 46% of their studies related to developmental disability or cognitive impairment; mental health was not a primary focus. A review of dramatherapy with CYPs experiencing a broad range of psychosocial problems has also been conducted (Berghs et al., 2022 ). While this review included some studies related to mental health, studies also related to CYPs with conditions such as Asperger's syndrome, conduct disorder and learning disability; mental health was not a primary focus.…”
Section: Introductionmentioning
confidence: 99%